2014
DOI: 10.3109/13880209.2014.936022
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification and validation of new peroxynitrite scavengers fromArtemisia iwayomogi

Abstract: Context: Artemisia iwayomogi Kitamura (Compositae) has been very widely used for the treatment of acute or chronic hepatitis, jaundice, and gastritis. In the course of our continuing efforts to identify and quantify peroxynitrite scavengers from Compositae plants, A. iwayomogi was used in this study. Objective: The present study was aimed to identify and quantify the peroxynitrite scavengers of A. iwayomogi. Materials and methods: Silica gel and ODS were used for column chromatography. The isolated compounds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
(32 reference statements)
0
5
0
1
Order By: Relevance
“…Although AIE did not show higher inhibition of cell growth than that of sorafenib in HCC, we observed that AIE had capacity to inhibit cell growth of HCC with less cytotoxicity in normal cells. Scopoletin and isochlorogenic acid B are well-known compounds of AI as previously reported [14,15]. For this reason, these compounds were used to standardize AIE.…”
Section: Resultsmentioning
confidence: 99%
“…Although AIE did not show higher inhibition of cell growth than that of sorafenib in HCC, we observed that AIE had capacity to inhibit cell growth of HCC with less cytotoxicity in normal cells. Scopoletin and isochlorogenic acid B are well-known compounds of AI as previously reported [14,15]. For this reason, these compounds were used to standardize AIE.…”
Section: Resultsmentioning
confidence: 99%
“…coffee, potatoes and apples, and natural products containing CGA have widely been used for the treatment of inflammation [9][10][11] . CGA exerts diverse biological activities, including anti-inflammatory, anti-oxidative and anti-neurotoxic activities [12][13][14][15].…”
mentioning
confidence: 99%
“…Compounds 2 and 3 were identified as steroids β ‐sitosterol 43 and stigmasterol, 43 respectively. Purification of ethyl acetate fraction on Sephadex LH‐20 CC afforded the flavonoids rutin ( 4 ), 44 2″‐ O ‐caffeoylrutin ( 5 ), 45 and hyperin ( 7 ) 46 . Compound 6 was identified as arbutin, a hydroquinone derivative 47,48 .…”
Section: Resultsmentioning
confidence: 99%